Effect of work environment and incentives giving on employee performance in Belimobilgue Bandung (Case Study in Belimobilgue Region Bandung Research Period 2020) - Ariestiana, Eka; Eka, Yelli (Technium Social Sciences Journal, 2021)
A company is an organization that brings together people who are commonly referred to as employees or employees to carry out household production activities of the company. Almost all companies have the goal of maximizing profits and value for the company, and improving the welfare of owners and employees. The development of a business is greatly influenced by the people in it. This study aims to find out how the work environment and incentives giving affect employee performance at the company Belimobilgue Region Bandung. Quantitative methods is used in this study, with a causal approach or cause and effect, to find out the effect of work environment variables (X1) and incentives (X2) on employee performance variables (Y). The population of this study were employees of the company Belimobilgue Bandung Region totaling 35 respondents. The data collecting was retrieved by using a questionnaire. The data were analyzed using multiple regression test, simultaneous test, partial test, and determination coefficient test, which were processed using SPSS Version 24 software. The results show that the work environment (X1) and incentives giving (X2) simultaneously have a significant effect on employee performance as evidenced by the results of the Sig. obtained work environment Sig value 0.001 <0.05, and the incentive Sig value 0.014 <0.05, as well as the R-Square value of 0.716. This means that the performance of employees of the company Belimobilgue Bandung Region is determined by the work environment and incentives of 71.6%, the remaining 28.6 is determined by other variables outside this model. Thus, the company Belimobilgue Bandung Region needs to pay attention to its work environment for its employees, and to give good incentives to employees who have good achievements in the company in order to improve the work performance.